Sustainable building design principles and practice - Keeping, Miles; Shiers, David (John Wiley & Sons, 2018)
An inside view of how one of the world's leading architecture and engineering practice does business Sustainable Built Environments: Principles and Practice offers detailed, environmentally sound design solutions to a wide range of building engineering challenges. The text uses case examples and project data provided by engineers and designers at Arup Associates. It covers a broad range of relevant issues, with focused commentaries and explanations presented in an accessible format for use by students, busy practitioners and informed clients. Whilst this book stresses the importance of a unified approach to design, the text is divided into six principal chapters, each addressing an important aspect of sustainable architecture and engineering. These chapters (Master Planning, Transport, Energy, The Building Envelope, Environmental Services, and Materials) may be read on their own or in sequence as part of a narrative. Throughout the book, photographs, architectural and engineering drawings and diagrams, examples, and other data illustrate the case studies. Numerous web links are provided to additional information. This inspirational book: Focuses on the work of Arup Associates, the award winning architectural and engineering practice Uses real-life examples of functioning buildings and structures to provide information and guidance on the development of sustainable solutions Is packed with informative illustrations Sustainable Built Environments: Principles and Practice is a unique text that will inform and inspire architects and engineers, as well as students of those disciplines, around the globe.
Includes bibliographical references. - Print version record
Keywords: Arup Associates; Sustainable buildings -- Design and construction; Sustainable construction; Construction durable; Sustainable buildings; Design and construction